Macroprudential policy and its impact on the credit cycle - De Schryder, Selien; Opitz, Frederic (Journal of Financial Stability, 2021)
We identify a novel set of macroprudential policy shocks and estimate their effects on credit cycle variables in a panel of 13 EU countries between 1999 and 2018. We find that a typical macroprudential policy tightening shock reduces bank credit-to-GDP by 2.4% points and household credit-to-GDP by 2.2% points over a period of four years. The non-financial corporations and total credit-to-GDP ratios, however, do not react significantly. Using state-dependent local projections, we further find that the effects on the credit-to-GDP ratios are stronger in credit cycle upturns than in downturns. We also detect a sizable leakage of firm credit from the banking to the non-banking sector next to a shift from household to firm credit.